2002
DOI: 10.1002/cncr.10577
|View full text |Cite
|
Sign up to set email alerts
|

Breast and cervical carcinoma screening practices among women in rural and nonrural areas of the United States, 1998–1999

Abstract: BACKGROUND Prior studies have suggested that women living in rural areas may be less likely than women living in urban areas to have had a recent mammogram and Papanicolau (Pap) test and that rural women may face substantial barriers to receiving preventive health care services. METHODS The authors examined both breast and cervical carcinoma screening practices of women living in rural and nonrural areas of the United States from 1998 through 1999 using data from the Behavioral Risk Factor Surveillance System.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
123
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(131 citation statements)
references
References 33 publications
6
123
1
Order By: Relevance
“…17,18 These findings are consistent with those of Saraiya et al, 4 who found that program providers were well poised to serve those women at the highest risk of cervical cancer because they were more likely than nonprogram providers to serve racially diverse, uninsured, publicly insured, and rural patients.…”
Section: Discussionsupporting
confidence: 82%
“…17,18 These findings are consistent with those of Saraiya et al, 4 who found that program providers were well poised to serve those women at the highest risk of cervical cancer because they were more likely than nonprogram providers to serve racially diverse, uninsured, publicly insured, and rural patients.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings that women living at home with family caregivers were less likely to receive Pap tests corroborates recent evidence that rates of preventive screenings are generally worse for adults with intellectual disabilities who live at home rather than in residential settings. 10,25 However, an unexpected 41,42 suggesting that further research is warranted. These findings suggest that (1) women with intellectual disabilities are not receiving cervical cancer screening at recommended rates or at rates similar to women without intellectual disabilities, (2) interventions to improve Pap test rates for women in the general population have failed to reach women with intellectual disabilities, and (3) there is a need for specialized screening guidelines for women with intellectual disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…A lower prevalence of Pap testing also tends to occur among rural populations. 19,[29][30][31][32] However, the interplay between socioeconomic factors, smoking, and Pap testing is complex because women who smoke, as a whole, may be more likely to engage in risky behavior, including a higher risk of exposure to HPV infection through a larger number of sexual partners. [33][34][35][36] The census data presented in Table 1 shows that KY, WV, and AL have similar rates of education and poverty, yet the rates of ICC are considerably lower in AL.…”
Section: Discussionmentioning
confidence: 99%